Factores de riesgo y complicaciones del embarazo en adolescentes que acuden al Hospital Regional Isidro Ayora de Loja - Cuenca Granda, Katherine Piedad (2015)
This research work was as purpose: to determine the population of teenage pregnancy of the study group, recognize the most important risk factors that occur during the teenage pregnancy and know the most frequent complications to develop in the course of adolescent pregnancy, it was descriptive, retrospective and cross-sectional, taking as study group to 97 pregnant adolescents who were treated in the areas of outpatient and hospitalization of the Gynecology Department - Obstetrics of the Regional Hospital Isidro Ayora of Loja, from June 1 until November 30 of 2014. The information was collected from the medical histories of the pregnant adolescents; where it was obtained the following results: 25.9 % of pregnant adolescents were served in the service of gynecology-obstetrics of the hospital; the 3.09 % of teenage pregnancies were at ages 10 to 14 years, low maternal weight was present in 27.84 % and 18.55 % distributed between overweight and obesity; 34.02 % of young pregnant women were unmarried; 7.22 % domestic workers, the 2.06 % did not have access to education. The 20.62 % of the pregnant teens have received less than 5 prenatal checkups; 26.80 % with a history of alcohol consumption and the 18.56 % with a history of tobacco consumption. The most frequent complications were: vaginal infections 23.71 %, threatened abortion 22.68 %, infection of the urinary tract 20.62 %, threat of childbirth pre term 17.53 %, anemia 7.22 %, premature rupture of membranes 4.12 % hemorrhage from the second half of pregnancy 2.06 % and hypertensive disorder 2.06 %. KEY WORDS: Teenage Pregnancy, risk factors, complications of pregnancy.